2016
DOI: 10.4081/rt.2016.6187
|View full text |Cite
|
Sign up to set email alerts
|

Importance of an Early Diagnosis in Primary Adenocarcinoma of the Seminal Vesicle

Abstract: The prognosis of seminal vesicle (SV) adenocarcinoma is often poor due to delayed diagnosis. About 95% of the patients die in less than 3 years. Diagnosis is difficult due to the absence of early clinical signs as hematuria, hematospermia and/or dysuria. We present the case of a 61-year-old Caucasian man with a left SV mass detected by transrectal ultrasound. SV ultrasound-guided biopsy showed an adenocarcinoma. The tumor was uniformly strongly immunoreactive for cytokeratin-7 and carcinoembryonic antigen. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Diagnostic difficulties include the absence of symptoms at an early stage and the lack of well-defined diagnostic criteria. 5 , 6 Symptoms in most cases are not specific, commonly: hematuria, hematospermia, pelvic/perineal pain and dysuria.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic difficulties include the absence of symptoms at an early stage and the lack of well-defined diagnostic criteria. 5 , 6 Symptoms in most cases are not specific, commonly: hematuria, hematospermia, pelvic/perineal pain and dysuria.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary neoplastic involvement of seminal vesicle is more frequent as compared with PSVA. Diagnosis is unlikely at an early stage due to the absence of symptoms and when the patients become symptomatic, they often suggest locally advanced disease masking the seminal vesicular origin of the tumour 3 5 6. It has been suggested that agenesis or dysgenesis of the kidneys with ectopic ureters exposes the epithelium of the seminal vesicles to carcinogens which could lead to PSVA in one or both the glands 7…”
Section: Discussionmentioning
confidence: 99%